Trickster Academy - Davis, Jenny L. (Jenny Lynn) (Book collections on Project MUSE., 2022)
"Trickster Academy is a full-length collection of poems that explore the experience of being Native in Academia-from land acknowledgement statements to the criteria for tenure and the histories of using Native American remains within Anthropology. Organized around the premise of the Trickster Academy, a university space run by and meant for training "tricksters," this collection moves between the personal dynamics of a two-spirit Indigenous woman in spaces where there are few others, and a "trickster's" critique of those same spaces. But these realities aren't specific only to those in academic positions-from leaving home, to being the only Indian in the room, to having to deal with the constant pressures to being a 'real Indian', they are shared experiences of Indians across many different regions, and all of us who live among tricksters"--